MODEL-BASED METHOD TO MEASURE THERMAL COMFORT IN BUILDINGS - Spasokukotskiy, Konstantyn; Trankler, Hans-Rolf; Lukasheva, Kateryna (International Journal of Computing, 2014)
This paper describes a practical method of measurement a HVAC control new variable. The method is based upon model-based estimation of thermal comfort. The thermal comfort is the only physical value, that truly corresponds to the changed (due to dynamic processing) environment conditions in buildings. The dynamic processing is a consequence of a modern demand-driven decentralized room climate control, that has been presented earlier, or a consequence of improvement of wall thermal insulation, that is beyond the limits of the actual insulation standards (for example 2002 - Energy saving regulations in Germany). The differences between various model types will be discussed. Some results will be shown for the realized model type.